The Chickpea, Summer Cropping, and a New Model for Pulse Domestication in the Ancient Near East - Abbo, S.; Shtienberg, D.; Lichtenzveig, Judith; Lev-Yadun, S.; Gopher, A. (The University of Chicago Press, 2003)
The widely accepted models describing the emergence of domesticated grain crops from their wild type ancestors are mostly based upon selection (conscious or unconscious) of major features related either to seed dispersal (nonbrittle ear, indehiscent pod) or free germination (nondormant seeds, soft seed coat). Based on the breeding systems (self-pollination) and dominance relations between the allelomorphs of seed dispersal mode and seed dormancy, it was postulated that establishment of the domesticated forms and replacement of the wild ancestral populations occurred in the Near East within a relatively short time. Chickpea (Cicer arietinum L.), however, appears as an exception among all other “founder crops” of Old World agriculture because of its ancient conversion into a summer crop. The chickpea is also exceptional because its major domestication trait appears to be vernalization insensitivity rather than pod indehiscence or free germination. Moreover, the genetic basis of vernalization response in wild chickpea (Cicer reticulatum Ladiz.) is polygenic, suggesting that a long domestication process was imperative due to the elusive phenotype of vernalization nonresponsiveness. There is also a gap in chickpea remains in the archaeological record between the Late Prepottery Neolithic and the Early Bronze Age. Contrary to the common view that Levantine summer cropping was introduced relatively late (Early Bronze Age), we argue for an earlier (Neolithic) Levantine origin of summer cropping because chickpea, when grown as a common winter crop, was vulnerable to the devastating pathogen Didymella rabiei, the causal agent of Ascochyta blight. The ancient (Neolithic) conversion of chickpea into a summer crop required seasonal differentiation of agronomic operation from the early phases of the Neolithic revolution. This topic is difficult to deal with, as direct data on seasonality in prehistoric Old World field crop husbandry are practically nonexistent. Consequently, this issue was hardly dealt with in the literature. Information on the seasonality of ancient (Neolithic, Chalcolithic, and Early Bronze Age, calibrated 11,500 to 4,500 years before present) Near Eastern agriculture may improve our understanding of the proficiency of early farmers. This in turn may provide a better insight into Neolithic agrotechniques and scheduling. It is difficult to fully understand chickpea domestication without a Neolithic seasonal differentiation of agronomic practice because the rapid establishment of the successful Near Eastern crop package which included wheats, barley, pea, lentil, vetches, and flax, would have preempted the later domestication of this rare wild legume.